EFEKTIVITAS INSTALASI PENJERNIH AIR TERHADAP KUALITAS AIR SUMUR DI JAMBANGAN SURABAYA - KURNIYAWATI (LenteraBio: Berkala Ilmiah Biologi, 2013)
Citizens of the pots using contaminated water wells to meet daily needs such as bathing, washing, cooking, watering and raw materials for drinking water. This research aims to test the effectiveness of water purification installation views of physical parameters required (temperature, and Total Disolved Solid), chemistry (pH) and based on the total number of Microbiology coliform and Fecal coliform. to improve the water quality. This research was observation using the approach of cross-sectional and target research is well water residents located next to the septic tank to be processed using simple water purification installation. Physical parameters observed were temperature and solids dissolved total, chemical parameters with degrees acidity (pH) and the parameters of microbiology with the amount of coliform bacteria total and Fecal coliform with the methods MPN. The data obtained were analyzed by qualitative and quantitative descriptive, then compared with Peraturan Pemerintah RI No. 82 tahun 2001 tentang Pengelolahan Kualitas Air dan Pengendalian Pencemaran Air. The results showed the Water Purification Installation can improve the quality of well water. This could be obsetved the total dissolved solids decreased from an average of 700mg/l, 434mg/l being, pH neutral, a decline in the number of total coliform is more than 2400 cells per 100 ml of cells to 140 and Fecal coliform 170 cells per 100 ml of cells to 26. standard meets the criteria so that clean of Peraturan Pemerintah RI No. 82 tahun 2001 tentang Pengelolahan Kualitas Air dan Pengendalian Pencemaran Air. . Key words: water purification installations; water quality analysis; Jambangan Surabaya